Two implant overdenture–the first alternative treatment for patients with complete edentulous mandible - Melescanu Imre, M (Carol Davila University Press, 2011)

(untitled)
Given the increasing life expectancy in the coming years, dental practitioners, as other specialists from different medical fields, will encounter an increasing number of complete edentulous patients. These patients, with a longer active life and higher standards of life quality, will have different expectations for their complete dentures, higher than the standard treatment that uses conventional complete dentures. Two–implant overdenture is considered the first alternative treatment in complete edentulous mandible, according to current medical standards established by a team of specialists in prosthodontics and implantology, and globally known as the McGill Consensus from McGill University, Montreal, Canada. The Consensus was established during a–dayߝand–a–half session of presentations done by experts who presented data, scientific information on the subject, and, not less significant, personal experiences of participants and patients. Overdenture on implants, as an alternative treatment for complete edentulous mandible, has multiple benefits in achieving better conditions of prosthesis: balance and effectiveness, with positive effects on oral structures, aesthetics, and quality of life. Mandibular two–implant overdenture, established as a standard treatment by the highest international forum, should gradually become the first choice of treatment in complete edentulous mandible.